USING OF VIRTUAL INTERACTIVE ENVIRONMENT IN COMPUTER SCIENCE - Turdybek А.А.; Abdildaeva А.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
We will conduct a practical and theoretical analysis of the virtual learning environment in computer science. Consider the goals and objectives of the study and analyze the effectiveness of training programs. We also discuss topical issues of "virtual technologies”," virtual interactive learning environment” and "online learning platform", etc. The scientific relevance of the work is due to the fact that modern technologies and virtual life affect children. Under the influence of globalization and informatization, new interactive approaches to teaching computer science have emerged. And virtual technologies are one of these ways. Virtual teaching in the country is not outdated. It is obvious that in the future, specialists working in this direction will need methodological guidance. After analyzing the results of the research work, I propose a manual for teachers. That is, to determine the practical significance of the research work and formulate rules for organizing and implementing a virtual interactive environment. In this project, we will look at ways to use and organize interactive computer technologies. Keywords: computer science, learning platform, educational process, IT technologies, virtual environment, programming languages, interactive learning.